GE_GERICHTE P/7705/2012 vom 18. Dezember 2012 - GE Cour de justice (2012)
; ADOLESCENT ; INJURE ; VOIES DE FAIT ; CLASSEMENT DE LA PROCÉDURE ; DIRECTIVE(INJONCTION) ; PEINE ; AUTORITÉ INFÉRIEURE | 3. PPMin; 30.PPMin; CPP.318; CPP.319; 21.PPMin; 26.PPMin; CPP.8; CPP.397